Effects of Parity on Service per Conception, Gestation Length, Milk Yield, Calving Interval, and Calf Birth Weight of Crossbred Dairy Cows - Abebe, Adane Shegaw (Archives of Veterinary Science, 2024)
Abstract The average lactation number for a stable herd dairy cow would be 3.4 and many dairy farmers do not keep dairy cows for extended lactation numbers beyond the 6th lactation number. Thus, there is a limited number of information focused on the later lactation number or parity (6-10) effect on lactation traits. Therefore, this study was conducted to evaluate the effect of lactation number on the number of services per conception, gestation length, lactation milk yield, lactation length, calving interval, and calve weight in crossbred Holstein Friesian cows. The record data at Haramaya University dairy farm was collected and compiled to assess the effects of lactation numbers. Retrospective data records of 1863, 1742, 1280, 1280, 1329, 1170, and 848 data of dairy cows were respectively used for evaluating the number of services per conception, gestation length, lactation length, lactation milk yield, calving interval, and calf birth weight. The study revealed that lactation number significantly affected the total lactation milk yield, lactation length, calving interval, and calf birth weight but it did not affect the number of services per conception and gestation length. Based on this study result, crossbred Holstein Friesian cows could be productive until the 8th lactation number without a significant decrease in the lactation milk yield. Therefore; lactation number should be used as an important trait in the performance of dairy cattle. Further study should be conducted to evaluate the effect of lactation number on other lactation traits such as dry period, days open, and milk composition. Keywords: Birth weight; Calving interval; Gestation; Lactation; Milk yield; Parity